Low-dose intravenous dexmedetomidine reduces shivering following cesarean delivery: a randomized controlled trial. (February 2021) - Sween, L.K.; Xu, S.; Li, C.; O'Donoghue, M.A.; Ciampa, E.J.; Kowalczyk, J.J.; Li, Y.; Hess, P.E.
Highlights: A randomized double-blind trial for prevention of post-cesarean shivering. Intravenous dexmedetomidine 10 µg was compared with placebo after delivery. Prophylactic dexmedetomidine 10 µg IV reduced post-cesarean shivering. No significant difference between dexmedetomidine and placebo for side effects. Dexmedetomidine may reduce the use of other anti-pruritic drugs. Abstract: Background: Intravenous dexmedetomidine 30 µg reduces shivering after cesarean delivery but can result in sedation and dry mouth. We hypothesized that prophylactic administration of 10 µg of IV dexmedetomidine would reduce the patient-reported severity of shivering after cesarean delivery, without an increased incidence of side effects. Methods: After institutional review board approval and informed written consent, women undergoing scheduled cesarean delivery with spinal or combined spinal-epidural anesthesia were randomized to receive either intravenous normal saline or dexmedetomidine 10 µg immediately after delivery. The primary outcome was a patient-rated subjective shivering score using a 10-cm visual analog scale at 30 and 60 min after arrival in the Post-Anesthesia Care Unit. Secondary outcomes included subjective scores for pain, nausea, itching, dry mouth, and sedation, as well as 24-h medication administration and investigator-rated observations of shivering, vomiting, pruritus, and sedation. Repeated measures ANOVA with Tukey-Kramer multiple-comparison test was applied for primary outcomes. Results: One hundred patients were enrolled, and 85 completed the study and were included in analysis. The mean ± SD shivering score in the dexmedetomidine group was significantly lower by repeated measures analysis than among controls across the first 60 min ( P =0.0002), and individually at both 30 and 60 min (placebo 1.8 ± 2.6 vs. dexmedetomidine 0.6 ± 1.4 at 30 min; 1.2 ± 2.1 vs. 0.3 ± 0.6 at 60 min; both P <0.01). Patient-rated and observer-rated side effects did not significantly differ between groups. Conclusions: Prophylactic administration of intravenous dexmedetomidine 10 µg after delivery reduces shivering without notable side effects.